Olive oil: maternal and pediatric health - Gianfranco Trapani; Liliana Vagliano; Marzia Giribaldi; Laura Cavallarin; Alessandra Coscia (Hygeia Press di Corridori Marinella, 2017)
The new base of the pyramid that represents the Mediterranean Diet (MD) includes a balanced lifestyle, healthy cooking methods, traditional, local and eco-friendly products, conviviality, physical activity with an adequate amount of rest, as well as caloric restriction and food frugality. Moreover, it has been confirmed that the main source of MD fat is Extra Virgin Olive Oil (EVOO). EVOO is considered a key feature of the healthy properties of the MD, due to its fatty acid, vitamin and polyphenol composition. However, these components need to be bioavailable to allow EVOO to exert its nutraceutical properties, which include antioxidant, anti-inflammatory, anti-cancer, antimicrobial, antiviral and hypoglycemic properties, as well as protective effects on the heart and brain, and during pregnancy and breast feeding. The main phenolic components responsible for the nutraceutical properties of EVOO are hydroxytyrosol, tyrosol and oleuropein. The adopted oil production and extraction technologies, such as extraction at low oxidative stress, determine the final polyphenol content in virgin olive oil. Limited information on the epigenetic effects of olive polyphenols is presently available, although the epigenetic effects of many other plant polyphenols have been well documented. In this context, it has been found that, if mothers consume an adequate amount of olive oil during pregnancy, their children will be exposed to a lower risk of wheezing in the first period of their lives. In addition, EVOO, because of its oleochantal content, a natural anti-inflammatory substance, may have an effect on many inflammatory diseases, even in the early period of life.